Antioxidant and anticholinergic properties of olivetol - Taslimi, Parham; Taslimi, Parham (Wiley, 2018)
Olivetol is a pioneer in diverse syntheses of tetrahydrocannabinol. It is produced by a type of insects, which is used as a pheromone, antiseptic, or repellent agent. In this study, we evaluated the antioxidant properties of olivetol using various methods including Fe3+-Fe2+ reducing, Cu2+-Cu+ reducing, Fe3+-TPTZ reducing, DPPH center dot scavenging, ABTS(center dot+) scavenging, DMPD center dot+ scavenging, superoxide radical scavenging, and Fe2+ chelating effects. The IC50 values of olivetol in the DPPH center dot, ABTS(center dot+), DMPD center dot+, O-2(center dot-), and metal chelating assays were 17.77, 1.94, 19.25, 53.30, and 2.83 mu g/mL, respectively. In this paper, olivetol showed excellent inhibitory effects against human (h) carbonic anhydrase (CA) isoforms I and II (hCA I and II), acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) enzymes. Both hCA isoenzymes were purified by sepharose-4B-L-tyrosine sulfanilamide affinity chromatography from fresh human blood erythrocytes. Olivetol demonstrated K-i values of 88.0511.15 nM against hCA I, 178.27 +/- 35.94 nM against hCA II, 3.40 +/- 0.34 nM against AChE and 2.73 +/- 0.18 nM against BChE, respectively.
Keywords: Acetylcholinesterase; Antioxidant activity; Butyrylcholinesterase; Carbonic anhydrase; Olivetol